Do reasons for undergoing bariatric surgery influence weight loss and health-related quality of life?–A Swedish mixed method study - Maria Jaensson; Emma Josefsson; Erik Stenberg; Karuna Dahlberg (PLoS ONE, 2022)
Background A wish for improved health or avoidance of ill health is often given as reason for wanting to undergo bariatric surgery. How such reasons relate to postoperative outcome is unclear. Objective The aim was to explore Swedish patients’ reasons for undergoing bariatric surgery. Also, we wanted to analyze if there were sex and age differences and associations with weight loss and health-related quality of life (HRQoL). Settings This was a single-center study conducted at a university hospital. Method Data on 688 patients (528 women and 160 men) including a free text response was analyzed inductively and deductively using predefined statements and was merged with data from the Scandinavian Obesity Surgery Registry. All data was analyzed using descriptive and analytic statistics. Result The most common reason for undergoing bariatric surgery was pain in different body parts. A wish for an improved medical condition was reported by most patients (59%, n = 408), followed by physical limitations making daily life difficult (42%, n = 288). Men and women reported similar reasons. Younger patients were more distressed about physical appearance (p = 0.001) and older patients wanted to improve their medical condition (p = 0.013). Health-related quality of life improved irrespective of reasons for undergoing surgery. Conclusion The most reported reasons for undergoing bariatric surgery were a wish for improved medical condition and to make daily life easier. Factors associated with the decision for surgery showed that there were few sex differences, but age seemed to be a factor. The HRQoL trajectory showed improvement regardless of reasons for undergoing surgery.